Influence of preceramic paper composition on microstructure and mechanical properties of spark plasma sintered Ti3SiC2-based composites; Journal of Physics: Conference Series; Vol. 1611 : Prospects of Fundamental Sciences Development (PFSD-2020) - Sedanova E. P. Elizaveta Pavlovna; Kashkarov E. B. Egor Borisovich; Syrtanov M. S. Maksim Sergeevich; Abdullina K. R. Kristina Rinatovna; Mingazova Yu. R. Yuliya Rafailovna; Lider A. M. Andrey Markovich; Travitsky (Travitzky) N. Nakhum (2020, 2020)
Title screen